2006
DOI: 10.1080/14685240600677673a
|View full text |Cite
|
Sign up to set email alerts
|

Joint multi-scale statistics of longitudinal and transversal increments in small-scale wake turbulence

Abstract: We analyse the relationship of longitudinal and transversal increment statistics measured in isotropic small-scale turbulence. This is done by means of the theory of Markov processes leading to a phenomenological Fokker-Planck equation for the two increments from which a generalized Kármán equation is derived. We discuss in detail the analysis and show that the estimated equation can describe the statistics of the turbulent cascade. A remarkable result is that the main differences between longitudinal and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 71 publications
(220 reference statements)
1
11
0
Order By: Relevance
“…It has been shown that for a higher dimensional analysis a corresponding non-vanishing q (2) 1 term violates the second von Kármán equation (see Eqs. (31) and (32) in [25]). In Fig.…”
Section: Results For Turbulencementioning
confidence: 98%
“…It has been shown that for a higher dimensional analysis a corresponding non-vanishing q (2) 1 term violates the second von Kármán equation (see Eqs. (31) and (32) in [25]). In Fig.…”
Section: Results For Turbulencementioning
confidence: 98%
“…Note that based on Taylor's hypothesis of frozen turbulence, these temporal correlations correspond to spatial ones. The directional dependency of these correlations may be expressed by a simple rescaling known for local isotropic small‐scale turbulence 7…”
Section: Velocity Increment Statistics For the Description Of Turbmentioning
confidence: 99%
“…2,6,8 The test begins with computing the total number of inversions, Q, after samples from a ¼ ½a 1 ; a 2 ; …; a m and b ¼ ½b 1 ; b 2 ; …; b n are merged as well as sorted in ascending order. An inversion occurs when adjacent ordered values in the combined matrix change from values provided from a to values provided by b or vice versa.…”
Section: -4 Melius Tutkun and Cal J Renewable Sustainable Enmentioning
confidence: 99%
“…One approach to characterize the statistics of small scale turbulence searches for the existence of Markov process. Markov processes have been discovered in several turbulent flows, such as high Reynolds number axisymmetric jet, 7 the wake behind a cylinder, 8 and fractal-generated grid turbulence. 9 In each of these studies, the flows demonstrated Markov process behavior for scales larger than or equal to the Taylor microscale, k, given by k 2 ¼ huðxÞ 2 i=hð @u @x Þ 2 i, where hÁi represents ensemble averaging.…”
Section: Introductionmentioning
confidence: 99%